Bentuk Penyajian Dan Fungsi Musik Nebah Tawak Dalam Upacara Notak Ompong Masyarakat Dayak Kebahan - siung, mickhel siung; Mastri Dihita Sagala; Chiristianly Yery Silaban (Magelaran: Jurnal Pendidikan Seni, 2024)
Nebah Tawak music is an integral part of the Notak Ompong ceremony, a tradition of the Dayak Kebahan community which is full of meaning where the groom leaves for the bride's house. Notak Ompong is a pre-wedding ceremony that always features Nebah Tawak music to accompany a traditional procession. However, this ceremony is rarely carried out in wedding processions. This research aims to reveal the form of presentation and function of Nebah Tawak music in the Notak Ompong ceremony. The research method uses qualitative methods to find out how the music is presented and what function it plays in the ceremony. Data was obtained through observation, interviews and documentation. The data analysis technique uses Miles and Huberman's theory, namely data reduction, data display, data presentation and drawing conclusions. Triangulation techniques were used to test the validity of the data, based on the results of observations, interviews and documentation. There is also triangulation of sources, namely descriptions of interviews with two musicians and traditional leaders. The results of the research show that Nebah Tawak music is presented with three Dayak gongs which have different sizes and tones. Nebah Tawak music presents cultural elements in it which are characteristic of the Dayak Kebahan community, so this music needs to be preserved. The function of Nebah Tawak music in the Notak Ompong ceremony is divided into three main aspects: as an accompaniment to traditional ceremonies, a means of entertainment for the community and as a representation of the cultural values of the Dayak Kebahan tribe.